Determinant of Willingness to Pay and Economic Value for Tourism Object using Contingent Valuation Method: The Case of Sangiran Sites, Province of Central Java, Indonesia - SUBANTI, Sri; HAKIM, Arif Rahman; IRAWAN, BRM Bambang; HAKIM, Inaki Maulida (Journal of Environmental Management and Tourism, 2017)
In this paper we want to determine the factors of willingness to pay for quality improvement and to estimates of economic value in Sangiran, Central Java Province, Indonesia. This paper used contingent valuation approach. The study involved Sangiran visitors, they were surveyed for their willingness to pay for historical, cultural, and educational function. Finding from this study, the significant factors affecting the individual’s willingness to pay are bid, gender, and income. The economic value of Sangiran sites tourism was estimated between Rp 0.665 billion per year until Rp 2.409 billion per year.